GUERRILLA MARKETING: DILEMA EFISIENSI BIAYA DAN EFEKTIFITAS PROMOSI DALAM MENDAPATKAN KONSUMEN - Retno Galih, Rizka Citra (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
Nowadays people’s knowledge is getting bigger, so it makesthe marketers have to develop their promotion technique becomesbetter for getting the increase number of the consumers. At first,guerrilla marketing is used by small business because it need not a bigfund but it is able to produce a lot of products. In real life, to do aguerrilla marketing strategy needs higher cost. Otherwise, there are alot of big companies which is used guerrilla marketing strategy. Whendoing guerrilla, especially the small enterprises they have to thinkabout the resource so that the enterprise can get the value ofconsumer that they want matched with the cost.Keywords : guerilla marketing, cost, promotion